The Comprehensive and Fundamental Analysis of the Application of Economic Value Added (EVA) in Tehran Stock Exchange) - Modanlo Joibary, Alireza (2020)
Economic value added (EVA) as a measure of performance is very useful. Calculation shows how and where a company creates wealth and value through the introduction of balance sheet items using this method. This will make managers aware of assets and costs when making managerial decisions. However, the calculation of economic value added strongly emphasizes the amount of investment capital and should be used for companies with stable or capitalized capital assets. The use of the Economic Value Added technique in companies with intangible assets such as technology companies and knowledge base may not be desirable. The present research objective is the fundamental analysis and application of Economic Value Added (EVA) in Tehran Stock Exchange.The result of the study illustrate  that  In model 1, EVA calculated by using dividend discount model (DDM) and  In model 2, EVA calculated by using Capital Asset Pricing Model (CAPM.).  The results show that average of EVA of listed companies of TSE in model 1 during 2005-2009 were -6931 and negative.The result of the study demonstrate  that  In model 2, EVA calculated by using WACC with CAPM model , average of EVA of listed companies of TSE in 2005-2009 periods were 80035 positive.